The Individual Features Of Indonesian-Chinese Mini-Novels - Feng, Ma (Lingua Cultura, 2011)
This article talks about mini-novels in the new period of Indonesian Chinese Literature. Through the overall developing trend of mini-novels’ corpuses, analyzes the individual creative features: firstly, the humor of Mo Mingmiao’s Mini-novels; secondly, the compassion of Xiao Xing’s Mini-novels; thirdly, Yuan Ni’s emotional sonata of The Lost Key-ring. By combination of themes and techniques of the three mini-novels corpuses, the article focuses on the analysis of three writers’ distinctive writing style.